Conservation and variation in the feeding mechanism of the spiny dogfish squalus acanthias - Wilga, C; Motta, P (Company of Biologists, 1998)
Changes in the feeding mechanism with feeding behavior were investigated using high-speed video and electromyography to examine the kinematics and motor pattern of prey capture, manipulation and transport in the spiny dogfish Squalus acanthias (Squalidae: Squaliformes). In this study, Squalus acanthias used both suction and ram behaviors to capture and manipulate prey, while only suction was used to transport prey. The basic kinematic feeding sequence observed in other aquatic-feeding lower vertebrates is conserved in the spiny dogfish. Prey capture, bite manipulation and suction transport events are characterized by a common pattern of head movements and motor activity, but are distinguishable by differences in duration and relative timing. In general, capture events are longer in duration than manipulation and transport events, as found in other aquatic-feeding lower vertebrates. Numerous individual effects were found, indicating that individual sharks are capable of varying head movements and motor activity among successful feeding events. Upper jaw protrusion in the spiny dogfish is not restricted by its orbitostylic jaw suspension; rather, the upper jaw is protruded by 30 % of its head length, considerably more than in the lemon shark Negaprion brevirostris (Carcharhinidae: Carcharhiniformes) (18 %) with its hyostylic jaw suspension. One function of upper jaw protrusion is to assist in jaw closure by protruding the upper jaw as well as elevating the lower jaw to close the gape, thus decreasing the time to jaw closure. The mechanism of upper jaw protrusion was found to differ between squaliform and carcharhiniform sharks. Whereas the levator palatoquadrati muscle assists in retracting the upper jaw in the spiny dogfish, it assists in protruding the upper jaw in the lemon shark. This study represents the first comprehensive electromyographic and kinematic analysis of the feeding mechanism in a squaliform shark.